Effect of electrochemical hydrogen charging on the mechanical property and corrosion behavior of Ti-3Mo alloy. (15th May 2022) - Pan, Zhimin; Wei, Ya; Fu, Yu; Luo, Hong; Li, Xiaogang
Abstract: The effect of electrochemical hydrogen charging on the mechanical property and corrosion behavior of Ti-3Mo alloy was investigated. Failure analysis revealed that the crack initiation and propagation were not along the crack tip of HICs although the existence of preferential cracking in α phase. The crack tended to propagate along the α/β interface rather than directly through α phase. Besides, i corr and i p increased with an increase in charging time from 0 h to 96 h, suggesting that hydrogen charging deteriorated the corrosion resistance of the matrix, which was attributed to the redox transformation process of the passive ﬁlm. Graphical Abstract: ga1 Highlights: The increase of the proportion of β phase reduces the sensitivity of hydrogen-induced cracking. Hydrogen-induced cracking (HIC) preferentially occures in the α phase. The redox mechanism of hydrogencauses the destablization of the oxide film. Crack propagation is not along the crack tip of HICs although the existence of preferential cracking in α phase.